PEMBERDAYAAN PEREMPUAN DALAM IKLAN NIKE WOMEN VERSI ‘WHAT WILL THEY SAY ABOUT YOU? - Kaniza Wibisono Sarwoko; Syafarina Tiyani Rianto; Jessica Elisabeth Kakiay (Jurnal Pustaka Komunikasi, 2022)
This Nike ad ‘What will they say about you?’ version, focus on female athletes who wear hijab so that they can carry out sports activities comfortably and do not need to think about the opinions of those around them who think that women wearing hijab are inappropriate to be athletes or do activities that are considered too masculine. This study aims to find and understand the meaning of the Nike ad ‘What will they say about you?’ version, through Roland Barthes's theory of Semiotics. This research used the qualitative interpretative method. The results of the study indicate that in the advertisement there are signs that have meaning directly or indirectly for the audience. Nike wants to show motivation and enthusiasm to all women, especially athletes who wear the hijab or to keep doing the sports they want without having to fear being judged by their social environment. With the tagline used in this advertising campaign, namely "Believe in More", Nike would like to say that, not all views, responses, or opinions against athletes are all bad and negative.